Development of self-healing vanillin/PEI hydrogels for tissue engineering - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (My University, 2023)
Self-healing materials recover mechanical damages to expand the lifetime of the material provided. In this study, self-healing hydrogels have been successfully prepared using a novel and simple technique. Vanillin is a natural monomer, used as a bio-based cross-linker for UV-induced bonding and Schiff-base bonding. Methacrylate-functionalized vanillin (M-VAN) is covalently integrated with the polymer matrix. While M-VAN supports polymer matrix with its vinyl group, its aldehyde functionality helps the formation of dynamic covalent imine bonds via Schiff-base formation. The hydrogel showed excellent self-healing ability overnight under physiological conditions without external addition. In addition, the hydrogel surface was modified by collagen and its cell viability was investigated. The prepared scaffolds showed good cell viability of 124% and 163% compared to the control sample. The developed self-healing material reveals that it has possible uses for future biomedical applications and tissue engineering studies due to the self-healing mechanism taking place under ambient conditions.
Keywords: Fizik; Astronomi ve Astrofizik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; Uzay bilimi; POLİMER BİLİMİ; KİMYA, ORGANİK; ASTRONOMİ VE ASTROFİZİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; SPACE SCIENCE; POLYMER SCIENCE; CHEMISTRY, ORGANIC; ASTRONOMY & ASTROPHYSICS; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Fizik ve Astronomi; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Physics and Astronomy; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; Hydrogels; Self-healing; UV-polymerization; Vanillin; Hydrogels; Self-healing; UV-polymerization; Vanillin